Cracks in the Boards: The Opportunity Cost of Governance Homogeneity - Helene Maghin (Center for Economic Studies and ifo Institute (CESifo), 2022)
Does the composition of governance affect firm outcomes? We exploit the timings and thresholds of a gender quota in boards of directors and supervisory boards to causally determine the impact of a change in leadership on performance. Using a novel design and data on boards, we find that firms forced to comply with the 2011 gender quota in France increased their profit margin by 5.4 percent relative to firms with unchanged boards thereby limiting diminishing profitability. We identify a shift in their cost structure away from purchasing of services such as out-sourcing and sub-contracting. In particular, we find evidence that firms change the type and the amount of external short-contract workers they hire. The decision to employ a lower amount of more qualified temporary workers is optimal as the firms' revenue grows. This in part reflects the importance of using domestic labour outsourcing to flexibly adjust to demand changes. We show that our effects are nearly entirely explained by the first newcomer in the board. The persistence of our estimates provide evidence for its role in updating knowledge. We find that the law is associated with the diversification of boards in terms of gender but also of nationality, age and links with other firms. The added value of within-board and network diversity suggest a sizable opportunity cost of governance homogeneity for performance.
Keywords: 330